(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The pharmaceutical industry plays a critical role in global healthcare by developing anddelivering innovative medicines to improve patient outcomes. To effectively reach healthcareprofessionals, patients, and other stakeholders, pharmaceutical companies employ various marketingstrategies. This study aims to explore and analyze the marketing strategies employed by the pharmaindustry and their impact on brand awareness, market penetration, and overall business performance.And the study in which discussed about Pharmaceutical Industry, Strategies Of PharmaceuticalIndustry, Factors Contributing to the Growth of the Pharmaceutical Market, Key Characteristics of theIndian Pharma Sector,Laws and Regulations Governing Indian Pharmaceuticals